2021
DOI: 10.3390/ma14112754
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Electrodeposition of Chitosan–AgNP Composites Using In Situ Coordination with Copper Ions

Abstract: Chitosan is an attractive material for biomedical applications. A novel approach for the anodic electrodeposition of chitosan–AgNP composites using in situ coordination with copper ions is proposed in this work. The surface and cross-section morphology of the obtained coating with varying concentrations of AgNPs were evaluated by SEM, and surface functional groups were analyzed with FT-IR spectroscopy. The mechanism of the formation of the coating based on the chelation of Cu(II) ions with chitosan was discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The physicochemical AgNPs' features, such as the small size of particles with large surface areas, allow them to penetrate cell walls and membranes and affect intracellular molecules, which leads to microbial cell death. This has been achieved in a variety of ways, including protein synthesis, metabolic pathway blockage, interference with the production of nucleic acid (DNA), and disruptions of the cell wall [9]. Some studies found that AgNPs may impact microbial resistance to antibiotics by affecting the genes that are responsible for the antibacterial activity because the nanoparticles could induce the break of single-strand DNA and affect gene expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical AgNPs' features, such as the small size of particles with large surface areas, allow them to penetrate cell walls and membranes and affect intracellular molecules, which leads to microbial cell death. This has been achieved in a variety of ways, including protein synthesis, metabolic pathway blockage, interference with the production of nucleic acid (DNA), and disruptions of the cell wall [9]. Some studies found that AgNPs may impact microbial resistance to antibiotics by affecting the genes that are responsible for the antibacterial activity because the nanoparticles could induce the break of single-strand DNA and affect gene expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the properties of CS and AgNPs, in this work a composite coating for AISI 304L steel was investigated. The traditional deposition methods of antibacterial coatings are electrophoretic deposition [42,43] and electrodeposition [44,45]. In this work to obtain the composite coating of CS/AgNPs we have used the galvanic deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is the study of the performances of CS/AgNPs coating in terms of corrosion protection of the metallic substrate in body fluid since the antibacterial behavior has been widely investigated in the literature [45,[61][62][63][64][65][66][67][68]. Austenitic stainless steels exhibit high corrosion resistance, and they are suitable to fabricate orthopedic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect to highlight is the deposition method adopted to coat the metal substrate. In particular, galvanic deposition was used because it is able to realize biocompatible coating [ 46 , 47 , 48 , 49 , 50 , 51 ]. The distinctive feature of this technique is that it does not require any external power supply.…”
Section: Introductionmentioning
confidence: 99%